Study on the role of gga-miRNA-200a in regulating cell differentiation and proliferation of chicken breast muscle by targeting Grb2. Issue 6 (2nd November 2017) - Jiang, Keren; Zhang, Meng; Li, Fang; Li, Donghua; Sun, Guirong; Liu, Xiaojun; Li, Hong; Han, Ruili; Jiang, Ruirui; Li, Zhuanjian; Kang, Xiangtao; Yan, Fengbin
ABSTRACT: Growth factor receptor-bound protein 2 (Grb2) have been proved by a lot of studies playing a major role in cell proliferation and cell differentiation. However, the regulation of Grb2 expression by microRNAs (miRNAs) in chicken breast muscle still remains unknown. The expression profile of Grb2 was checked based on our previous RNA sequencing data and the Grb2 relative expression level in breast muscle of aged hens (55-week-old) was validated significantly higher than juvenile hens (20-week-old) using qRT-PCR. miRNAs that interact with Grb2 have been predicted in chicken and the relationship between the potential miRNA and Grb2 was verified using dual luciferase reporter assay in chicken DF1 cells. Dual-luciferase reporter assays results demonstrated that the expression of luciferase reporter gene linked with part sequence of the 3′UTR of chicken Grb2 gene was down-regulated by the overexpression of gga (Gallus Gallus)-miR-200a-3p in the DF1 cells, and the down-regulation behavior was abolished when the gga-miR-200a-3p binding site in 3′UTR of Grb2 was mutated, indicating that gga-miR-200a can suppress the expression level of its target gene Grb2. Therefore, we concluded that the significantly increased expression level of Grb2 in the breast muscle of aged chicken can (at least partly can) be explained by the decreased expression of miR-200a, which reduced the inhibitory effect on Grb2. Taken together, these findings suggest that gga-miR-200a can suppress the expression level of its target gene Grb2 and might be involved in the cell differentiation and proliferation of chicken breast muscle through binding with the 3'UTR of Grb2.